Speeding up or Slowing Down? Analysis of Race Results in Elite-level Swimming from 2011-2019 to Predict Future Olympic Games Performances. Issue 2 (3rd April 2022) - Crowley, Emmet; Ng, Kwok; Mujika, Iñigo; Powell, Cormac
ABSTRACT: The aim of this study was to examine the trends in Olympic Games (OLY) and World Long Course Championships (WLC) across three performance categories (1 st -3 rd, 4 th -8 th and 9 th -16 th ), and to make predictions for the 2024 OLY. Top 16 rankings were obtained for all OLY and WLC competitions between 2011 and 2019. Linear regression and forecasting models were used to examine trends and predictions. A total of 3, 061 individual race results were included. For both genders, significant changes were observed in 13 of 14 Olympic events, with most changes highlighting those events have improved (mean: −0.72% (± 0.81%) for Men; −0.60% (± 0.81%) for Women). For the 2024 predictions, events fall into five groups: improving; declining; converging; diverging; and stable. These results offer insights about trends in times required to be a semi-finalist, finalist, and medalist. This, coupled with the 2024 predictions, may allow high-performance programs to target specific OLY events.